Antibodies Toward Vedolizumab Appear from the First Infusion Onward and Disappear Over Time. Issue 12 (December 2017) - Bian, Sumin; Dreesen, Erwin; Tang, Ho Tsun; Compernolle, Griet; Peeters, Miet; Van Assche, Gert; Ferrante, Marc; Vermeire, Séverine; Gils, Ann
Abstract : Background: Vedolizumab (VDZ) has been approved for the treatment of patients with moderate-to-severe Crohn's disease and ulcerative colitis. The GEMINI trials reported a low prevalence of anti-VDZ antibodies (AVA). However, the AVA assays used in GEMINI were drug sensitive, resulting in a possible underestimation of the rate of AVA formation. This study aimed to monitor immunogenicity of VDZ in a real-life cohort using a drug-resistant AVA assay. Methods: Using a combination of VDZ/AVA complex precipitation and acid dissociation, a drug-resistant assay for AVA detection in the presence of high VDZ concentrations has been developed and analytically validated. The assay was applied on serum samples of 179 VDZ-treated patients with inflammatory bowel disease to evaluate the prevalence and time course of AVA. Results: A dose–response curve ranging from 25 to 1600 ng/mL using 1/125 diluted serum was obtained, allowing the detection of AVA concentrations up to 200 μg/mL of MA-VDZ19C11 equivalents, a calibrator antibody to VDZ. This assay was highly AVA specific and drug resistant. Four of 179 VDZ-treated patients (2.2%) were AVA positive and AVA were detected already after the first VDZ infusion. AVA were all transient in these patients without need for any dosage optimization. There was no correlation between VDZ and AVA concentrations in the AVA-positive samples. Conclusions: AVA appear from the first VDZ infusion onward and disappear over time. The low prevalence of AVA suggests that immunogenicity does not influence response to treatment. Abstract : Article first published online 29 September 2017.